Argumentstruktur und aspektuelle Komposition im Georgischen - Rostovtsev-Popiel, Alexander (Georgica, 2016)
From a functional-typological perspective, the paper examines the interaction models of the grammatical categories of the Georgian verb. The study emphasises the interaction between the verbal argument structure and aspectual characteristics. The following issues are discussed in depth: (1) Why does the Georgian word-form offer an actual or progressive “reading” of specific valency derivatives? (2) Do the morphosyntactic properties of the verb influence its aspectual reinterpretation? And if they do, then (3) what factors determine the atelicity, resultativity, or other features of grammatical meaning in the corresponding reinterpretation that cannot be explained using the currently known categories of the Georgian verb?